Biomass briquetting reduces the energy loss during long-term ensiling and enhances anaerobic digestion: A case study on rice straw. (November 2019) - Ai, Ping; Zhang, Xiuzhi; Ran, Yi; Meng, Liang; Elsayed, Mahdy; Fan, Qizhou; Abomohra, Abd El-Fatah
Graphical abstract: Highlights: The effect of rice straw briquetting prior to ensiling was studied. Long-term ensiling reduced total solids (TS) and volatile solids (VS). Briquetting diminished TS and VS loss, while enhanced cellulose and hemicellulose. Shortest ensiling and maximum briquetting showed highest cumulative biogas yield. Briquetting prior to ensiling is a favorable approach to enhance biogas yield. Abstract: The present study evaluated the impact of briquetting prior to ensiling on rice straw characteristics and anaerobic digestion performance. Ensiling for 10 months significantly reduced cellulose, hemicellulose and lignin of the uncompressed straw by 50.3%, 61.6% and 34.6%, respectively. However, increase of briquetting ratio enhanced the cellulose and hemicellulose contents at different ensiling times. In addition, increasing of ensiling time significantly reduced the biogas yield, while the highest cumulative biogas yield of 313.8 L kg −1  VS was obtained from rice straw ensiled for 7 days at 1:6 briquetting ratio. Interestingly, the maximum biogas productivity of 1:6 briquetted straw after 10 months ensiling was 17.7% higher than that of the uncompressed straw ensiled for 7 days. Thus, briquetting prior to ensiling is a favorable approach to reduce the mass loss for enhanced biogas yield and energy recovery.